La montee du protectionnisme. (Pamphlet Series, 1978)
This paper examines the recent trend of rise in protectionism policy in many countries. The general trend of commercial policy during the postwar era was toward a liberal world trading system. In contrast to this trend, pressures for protection have emerged in many countries recently, and it seems probable that the pressures for protectionism will continue. If these pressures are given in to, the consequences for the international economy will become increasingly serious, especially for developing and other primary producing countries whose development and industrialization are affected.